A Brief Research Report on the Perception and Satisfaction of Italian University Students With Disabilities and Specific Learning Disabilities at the Emergency Remote Teaching During the COVID-19 Lockdown - Carpinelli, Luna; Bruno, Giorgia; Savarese, Giulia (Frontiers in Education, 2021)
Introduction: The COVID-19 pandemic has inevitably transformed face-to-face teaching to remote teaching (e-learning or blended) which has had psychological and social impacts on the mental health of university students. Object: In this study, we surveyed university students with disabilities and specific learning disabilities (SLDs) on their perceptions of and satisfaction with emergency remote teaching (ERT) during the lockdown phase (March–April 2020) and following restrictions due to the COVID-19 pandemic. We compared the responses of students with disabilities and SLDs with those of normotypical students. Methodology: A questionnaire was completed remotely: five items on the ERT were designed as ad hoc questions and five items were taken from the Short Form 12 Health Survey (SF-12) to evaluate physical and mental self-perceived health. There was a total of 163 students surveyed, 67 students with disabilities and/or SLDs and 96 normotypical students. Results and Conclusion: Students with disabilities and SLDs were more satisfied with remote teaching than the normotypical students. In fact, only 22% of the students with disabilities or SLDs indicated that they were dissatisfied with the teaching method used due to difficulties encountered, including those related to a weak technological infrastructure. We found that among all the students, important social and emotional aspects emerged as a consequence of the absence of interactions and relationships with both faculty and peer groups.